A field system for measuring plant and soil carbon fluxes using stable isotope methods - McCloskey, Christopher S.; Otten, Wilfred; Paterson, Eric; Ingram, Benjamin R.; Kirk, Guy J. D. (Wiley, 2020)
There is a lack of field methods for measuring plant and soil processes controlling soil organic matter (SOM) turnover over diurnal, seasonal, and longer time-scales with which to develop datasets for modelling. We describe an automated field system for measuring plant and soil carbon fluxes over such time-scales using stable isotope methods, and we assess its performance. The system comprises 24 large (1-m deep, 0.8-m diameter) cylindrical lysimeters connected to gas-flux chambers and instruments. The lysimeters contain intact, naturally-structured C3 soil planted with a C4 grass. Fluxes of CO2 and their 13C isotope composition are measured 3-times daily in each lysimeter, and the isotope composition is used to partition the fluxes between plant and soil sources. We investigate the following potential sources of error in the measurement system and show they do not significantly affect the measured CO2 fluxes or isotope signatures: gas leaks; the rate of gas flow through sampling loops; instrument precision and drift; the concentration-dependence of isotope measurements; and the linearity of CO2 accumulation in the chambers and associated isotope fractionation resulting from different rates of 13CO2 and 12CO2 diffusion from the soil. For the loamy grassland soil and US prairie grass (Bouteloua dactyloides) tested, the precision of CO2 flux measurements was ± 0.04 % and that of the flux partitioning ± 0.40 %. We give examples of diurnal and seasonal patterns of plant and soil C fluxes and soil temperature and moisture. We discuss the limitations of the isotope methodology for partitioning fluxes as applied in our system. We conclude the system is suitable for measuring net ecosystem respiration fluxes and their plant and soil components with sufficient precision to resolve diurnal and seasonal patterns
Keywords: soil organic matter; lysimeter; C4 photosynthesis